2009
DOI: 10.1111/j.1365-2818.2008.03107.x
|View full text |Cite
|
Sign up to set email alerts
|

EBSD: a powerful microstructure analysis technique in the field of solidification

Abstract: SummaryThis paper presents a few examples of the application of electron back-scatter diffraction (EBSD) to solidification problems. For directionally solidified Al-Zn samples, this technique could reveal the change in dendrite growth directions from <100> to <110> as the composition of zinc increases from 5 to 90 wt%. The corresponding texture evolution and grain selection mechanisms were also examined. Twinned dendrites that form under certain solidification conditions in Al-X specimens (with X = Zn, Mg, Ni,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…a stereographic projection of observed crystallographic directions. [19] Solidified, spherical samples were overcasted with numerous fine geodesics resembling the mesh of lattitudes and longitudes on a globe. Ten longitudes meet at two poles marking the onset point of solidification and its antipode, allowing for an oriented embedding.…”
mentioning
confidence: 99%
“…a stereographic projection of observed crystallographic directions. [19] Solidified, spherical samples were overcasted with numerous fine geodesics resembling the mesh of lattitudes and longitudes on a globe. Ten longitudes meet at two poles marking the onset point of solidification and its antipode, allowing for an oriented embedding.…”
mentioning
confidence: 99%
“…2 reveal the expected qualitative differences of the quasicrystal solidification near the sample edge compared to the center region, we investigated these two areas by EBSD using pattern matching to the experimental Kikuchi standard. For an overview of applications of EBSD in the field of solidification, see 27 .…”
Section: Microtexture Of a Quasicrystalline Materialsmentioning
confidence: 99%
“…This found that the [0001] direction in the HCP oxide was parallel to the [001] direction in the FCC substrate, albeit this was defined from a limited number of cases given the significant complexity in making these measurements. The inherently surface sensitive nature of the technique proposed coupled with the EBSD measurements permits more extensive insight into these observations and the potential for similar approaches with other cubic systems (11,73,110,112).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions were fixed to produce the required thickness of alumina on the surface in the same way as mentioned by (31,112,118 proves the ¼ wave plate thickness and wavelength are suitable. (85,92,120,122).…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation